the A journey of the risks of the work accidents behind the door of offices and factories، from challenges to strategies to confront them "The French experience Model 1800 – 1913"(Historical study) (Journal of Human Sciences, 2025)
This research aims to identify work hazards and accidents in France during the period between 1800 and 1913 by clarifying the risks and harms of work. y clarifying the concept of occupational hazards and harms، and studying the categories of occupational victims according to gender، age، and types of professions to identify the risk factors that can cause an occupational accident in the workplace، in addition to highlighting the efforts made to eliminate occupational hazards. Occupational hazards pose a major threat in the field of professions and industries، as they cause physical and psychological pain for workers and burden societies economically and socially. However, eliminating them is not impossible if there is a strong political will, societal awareness، culture and leadership. The labor movement، trade unions and other concerned parties have played a major role in confronting the health risks that workers are exposed to in their work environments، which has prompted authorities and political parties to pay attention to protecting workers and proposing ways to improve their health and physical and psychological safety through numerous laws، constantly updating them and paying attention to safety programs for a secure professional future.